Donor–acceptor type co-crystals of arylthio-substituted tetrathiafulvalenes and fullerenes - Lu, Xiaofeng; Sun, Jibin; Zhang, Shangxi; Ma, Longfei; Liu, Lei; Qi, Hui; Shao, Yongliang; Shao, Xiangfeng (Beilstein Journal of Organic Chemistry, 2015)
A series of donor–acceptor type co-crystals of fullerene (as the acceptor) and arylthio-substituted tetrathiafulvalene derivatives (Ar-S-TTF, as the donor) were prepared and their structural features were thoroughly investigated. The formation of co-crystals relies on the flexibility of Ar-S-TTF and the size matches between Ar-S-TTF and fullerene. Regarding their compositions, the studied co-crystals can be divided into two types, where types I and II have donor:acceptor ratios of 1:1 and 1:2, respectively. Multiple intermolecular interactions are observed between the donor and acceptor, which act to stabilize the structures of the resulting co-crystals. In the type I co-crystals, the fullerene molecule is surrounded by four Ar-S-TTF molecules, that is, two Ar-S-TTF molecules form a sandwich structure with one fullerene molecule and the other two Ar-S-TTF molecules interact with the fullerene molecule along their lateral axes. In the type II co-crystals, one fullerene molecule has the donor–acceptor mode similar to that in type I, whereas the other fullerene molecule is substantially surrounded by the aryl groups on Ar-S-TTF molecules and the solvent molecules.
Keywords: arylthio-substituted tetrathiafulvalene; co-crystal; donor–acceptor system; fullerene

(untitled) - Wudl, F.; Smith, G. M.; Hufnagel, E. J. (J. Chem. Soc. D, 1970)

(untitled) - Coffen, D. L.; Chambers, J. Q.; Williams, D. R.; Garrett, P. E.; Canfield, N. D. (J. Am. Chem. Soc., 1971)

(untitled) - Hünig, S.; Kiesslich, G.; Scheutzow, D.; Zahradnik, R.; Carsky, P. (Int. J. Sulfur Chem., Part C, 1971)

Organic Superconductors (including Fullerenes) - Williams, J. M.; Ferraro, J. R.; Thorn, R. J.; Carlson, K. D.; Geiser, U.; Wang, H. H.; Kini, A. M.; Whangbo, M. H. (Prentice Hall, 1992)

Organic Superconductors - Ishiguro, T.; Yamaji, K.; Saito, G. (Springer, 1998)

Molecular Conductors - Batail, P. (Chem. Rev., 2004)

Organic Conductors - Kagoshima, S.; Kanoda, K.; Mori, T. (J. Phys. Soc. Jpn., 2006)

The Physics of Organic Superconductors and Conductors - Lebed, A. (Springer, 2008)

(untitled) - Ardavan, A.; Brown, S.; Kagoshima, S.; Kanoda, K.; Kuroki, K.; Mori, H.; Ogata, M.; Uji, S.; Wosnitza, J. (J. Phys. Soc. Jpn., 2012)

(untitled) - Ferraris, J.; Cowan, D. O.; Walatka, V.; Perlstein, J. H. (J. Am. Chem. Soc., 1973)

(untitled) - Jérome, D.; Mazaud, A.; Ribault, M.; Bechgaard, K. (J. Phys., Lett., 1980)

(untitled) - Bryce, M. R. (Chem. Soc. Rev., 1991)

(untitled) - Adam, M.; Müllen, K. (Adv. Mater., 1994)

(untitled) - Jørgensen, T.; Hansen, T. K.; Becher, J. (Chem. Soc. Rev., 1994)

(untitled) - Garían, J. (Adv. Heterocycl. Chem., 1995)

(untitled) - Coronado, E.; Gómez-García, C. J. (Chem. Rev., 1998)

(untitled) - Bryce, M. R. (Adv. Mater., 1999)

(untitled) - Nielsen, M. B.; Lomholt, C.; Becher, J. (Chem. Soc. Rev., 2000)

(untitled) - Segura, J. L.; Martín, N. (Angew. Chem., Int. Ed., 2001)

(untitled) - Bendikov, M.; Wudl, F.; Perepichka, D. F. (Chem. Rev., 2004)

(untitled) - Frère, P.; Skabara, P. J. (Chem. Soc. Rev., 2005)

(untitled) - Canevet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Martín, N.; Sánchez, L.; Seoane, C.; Andreu, R.; Garín, J.; Orduna, J. (Tetrahedron Lett., 1996)

(untitled) - Martín, N.; Sánchez, L.; Herranz, M. Á.; Guldi, D. M. (J. Phys. Chem. A, 2000)

(untitled) - Giacalone, F.; Segura, J. L.; Martín, N.; Guldi, D. M. (J. Am. Chem. Soc., 2004)

(untitled) - Fernández, G.; Pérez, E. M.; Sánchez, L.; Martín, N. (Angew. Chem., Int. Ed., 2008)

(untitled) - Fernández, G.; Pérez, E. M.; Sánchez, L.; Martín, N. (J. Am. Chem. Soc., 2008)

(untitled) - Pérez, E. M.; Sánchez, L.; Fernández, G.; Martín, N. (J. Am. Chem. Soc., 2006)

(untitled) - Pérez, E. M.; Sierra, M.; Sánchez, L.; Torres, M. R.; Viruela, R.; Viruela, P. M.; Ortí, E.; Martín, N. (Angew. Chem., Int. Ed., 2007)

(untitled) - Fernández, G.; Sánchez, L.; Pérez, E. M.; Martín, N. (J. Am. Chem. Soc., 2008)

(untitled) - Isla, H.; Gallego, M.; Pérez, E. M.; Viruela, R.; Ortí, E.; Martín, N. (J. Am. Chem. Soc., 2010)

(untitled) - Huerta, E.; Isla, H.; Pérez, E. M.; Bo, C.; Martín, N.; de Mendoza, J. (J. Am. Chem. Soc., 2010)

(untitled) - Grimm, B.; Santos, J.; Illescas, B. M.; Muñoz, A.; Guldi, D. M.; Martín, N. (J. Am. Chem. Soc., 2010)

(untitled) - Canevet, D.; Gallego, M.; Isla, H.; de Juan, A.; Pérez, E. M.; Martín, N. (J. Am. Chem. Soc., 2011)

(untitled) - Fukuzumi, S.; Ohkubo, K.; Kawashima, Y.; Kim, D. S.; Park, J. S.; Jana, A.; Lynch, V. M.; Kim, D.; Sessler, J. L. (J. Am. Chem. Soc., 2011)

(untitled) - Zhou, Z.; Qin, Y.; Xu, W.; Zhu, D. (Chem. Commun., 2014)

(untitled) - Nielsen, K. A.; Cho, W.-S.; Sarova, G. H.; Petersen, B. M.; Bond, A. D.; Becher, J.; Jensen, F.; Guldi, D. M.; Sessler, J. L.; Jeppesen, J. O. (Angew. Chem., Int. Ed., 2006)

(untitled) - Izuoka, A.; Tachikawa, T.; Sugawara, T.; Suzuki, Y.; Konno, M.; Saito, Y.; Shinohara, H. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Konarev, D. V.; Semkin, V. N.; Graja, A.; Lyubovskaya, R. N. (J. Mol. Struct., 1998)

(untitled) - Saito, G.; Sasaki, H.; Aoki, T.; Yoshida, Y.; Otsuka, A.; Yamochi, H.; Drozdova, O. O.; Yakushi, K.; Kitagawa, H.; Mitani, T. (J. Mater. Chem., 2002)

(untitled) - Konarev, D. V.; Khasanov, S. S.; Saito, G.; Otsuka, A.; Lyubovskaya, R. N. (J. Mater. Chem., 2007)

(untitled) - Pérez, E. M.; Marín, N. (Chem. Soc. Rev., 2008)

TTF Chemistry: Fundamentals and Applications of Tetrathiafulvalenes - Yamada, J.; Sugimoto, T. (Springer, 2004)

(untitled) - Hervé, K.; Liu, S.-X.; Cador, O.; Golhen, S.; Gal, Y. L.; Bousseksou, A.; Stoeckli-Evans, H.; Decurtins, S.; Ouahab, L. (Eur. J. Inorg. Chem., 2006)

(untitled) - Jia, C.; Liu, S.-X.; Tanner, C.; Leiggener, C.; Neels, A.; Sanguinet, L.; Levillain, E.; Leutwyler, S.; Hauser, A.; Decurtins, S. (Chem. – Eur. J., 2007)

(untitled) - Murata, T.; Morita, Y.; Yakiyama, Y.; Fukui, K.; Yamochi, H.; Saito, G.; Nakasuji, K. (J. Am. Chem. Soc., 2007)

(untitled) - Zhu, Q.-Y.; Liu, Y.; Lu, W.; Zhang, Y.; Bian, G.-Q.; Niu, G.-Y.; Dai, Y. (Inorg. Chem., 2007)

(untitled) - Wu, J.-C.; Liu, S.-X.; Keene, T. D.; Neels, A.; Mereacre, V.; Powell, A. K.; Decurtins, S. (Inorg. Chem., 2008)

(untitled) - Fujiwara, H.; Sugishima, Y.; Tsujimoto, K. (Tetrahedron Lett., 2008)

(untitled) - Zhu, Q.-Y.; Huo, L.-B.; Qin, Y.-R.; Zhang, Y.-P.; Lu, Z.-J.; Wang, J.-P.; Dai, J. (J. Phys. Chem. B, 2010)

(untitled) - Jaggi, M.; Blum, C.; Marti, B. S.; Liu, S.-X.; Leutwyler, S.; Decurtins, S. (Org. Lett., 2010)

(untitled) - Mitamura, Y.; Yorimitsu, H.; Oshima, K.; Osuka, A. (Chem. Sci., 2011)

(untitled) - Lincke, K.; Frellsen, A. F.; Parker, C. R.; Bond, A. D.; Hammerich, O.; Nielsen, M. B. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ueno, R.; Fujino, D.; Yorimitsu, H.; Osuka, A. (Chem. – Eur. J., 2013)

(untitled) - Yamashita, Y.; Kobayashi, Y.; Miyashi, T. (Angew. Chem., Int. Ed. Engl., 1989)

(untitled) - Christensen, C. A.; Batsanov, A. S.; Bryce, M. R. (J. Org. Chem., 2007)

(untitled) - Kato, T.; Origuchi, C.; Shinoda, M.; Adachi, C. (Jpn. J. Appl. Phys., 2011)

(untitled) - Yamashita, M.; Kuzuhara, D.; Aratani, N.; Yamada, H. (Chem. – Eur. J., 2014)

(untitled) - Nielsen, K. A.; Cho, W.-S.; Jeppesen, J. O.; Lynch, V. M.; Becher, J.; Sessler, J. L. (J. Am. Chem. Soc., 2004)

(untitled) - Sun, J.; Lu, X.; Shao, J.; Cui, Z.; Shao, Y.; Jiang, G.; Yu, W.; Shao, X. (RSC Adv., 2013)

(untitled) - Sun, J.; Lu, X.; Shao, J.; Li, X.; Zhang, S.; Wang, B.; Zhao, J.; Shao, Y.; Fang, R.; Wang, Z.; Yu, W.; Shao, X. (Chem. – Eur. J., 2013)

(untitled) - Lu, X.; Sun, J.; Liu, Y.; Shao, J.; Ma, L.; Zhang, S.; Zhao, J.; Shao, Y.; Zhang, H.-L.; Wang, Z.; Shao, X. (Chem. – Eur. J., 2014)

(untitled) - Sun, J.; Lu, X.; Ishikawa, M.; Nakano, Y.; Zhang, S.; Zhao, J.; Shao, Y.; Wang, Z.; Yamochi, H.; Shao, X. (J. Mater. Chem. C, 2014)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

(untitled) - Krätschmer, W.; Lamb, L. D.; Fostiropoulos, K.; Huffman, D. R. (Nature, 1990)

(untitled) - Hawkins, J. M.; Lewis, T. A.; Loren, S. D.; Meyer, A.; Heath, J. R.; Saykally, R. J.; Hollander, F. J. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Tanigaki, K.; Prassides, K. (J. Mater. Chem., 1995)